PENGARUH GOOD CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN INDONESIA YANG MASUK DALAM ASEAN CORPORATE GOVERNANCE SCORECARD - Wieta Chairunesia; Putri Renalita Sutra; Sely Megawati Wahyudi (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The era of globalization requires companies that have go public have a competitive advantage and strong competitiveness to survive in the capital market. Companies are not only required to produce quality products for consumers, but also have good corporate governance (corporate governance), meaning the company's management policy should be able to ensure the sustainability of the business. Profit becomes one of the important factors for investors so managers often use profit as engineering targets. This profit engineering is known as earnings management. In addition to Good Corporate Governance there are other factors that influence managers to perform earnings management ie financial distress. This research is aimed to find out the influence of good corporate governance and financial distress to earnings management in Indonesian companies which are included in ASEAN corporate governance scorecard. The type of research used is quantitative and the research sample is determined based on purposive sampling. The analytical method used by using the analysis tool is multiple linear regression. The results showed that the coefficient of determination adjusted for 0.173 means 17.3% variable Earnings Management is influenced by Good Corporate Governance and Financial distress variables. While the remaining 82.7% influenced by other factor. Result of F test that simultaneously variable of Good Corporate Governance and Financial distress have significant influence to earnings management variable. The result of partial variable t test of Good Corporate Governance has no effect to Profit Management. While the Financial Distress has a positive and significant impact on Profit Management.